EFEKTIFITAS PENGELOLAAN LABORATORIUM IPA - Elseria Elseria (Manajer Pendididikan, 2016)
This study evaluated the management of science laboratories at Junior High School Number 1 Kepahiang. The subjects of this research are principal, laboratory coordinator, laboratory staff, Physics and Biology teachers. Data are collected by questionnaire, interview, observation, and documentation. The results of this study indicate that the management of thescience laboratory has been done effectively. Management of infrastructure and facilities already met to the laboratory standard, and supporting the effectiveness of science laboratory, completeness of administrative form also conform with the standard prescribed which has been functioned as it should. Monitoring and evaluation has been carried out in conducive and sustainable. Based on this study, researcher concluded that the management of the Science Laboratory at Junior High School Number 1 has been done effective.Keywords: management, laboratory, effectivity.